2013
DOI: 10.1080/02680513.2013.796286
|View full text |Cite
|
Sign up to set email alerts
|

Open educational practices for curriculum enhancement

Abstract: Open educational resources (OER) and open educational practices (OEP) are relatively new areas in educational research. How OER and OEP can help practitioners enhance curricula is one of a number of under-researched topics. This article aims to enable practitioners to identify and implement appropriate open practices to enhance higher education curricula. To that aim, we put forward a framework of four open educational practices based on patterns of OER reuse ('as-is' or adapted), mapped against the processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
0
31
0
1
Order By: Relevance
“…Research studies deal with this broad definition of OEP in various ways. Some focus primarily on the OER aspects of OEP (Armellini & Nie, 2013;Atenas, Havemann, & Priego, 2014;Hogan, Carlson, & Kirk, 2015;Karunanayaka, Naidu, Rajendra, & Ratnayake, 2015;Murphy, 2013;Schreurs et al, 2014). Other studies explore broader aspects of OEP such as open pedagogies and learning in open networks (Casey & Evans, 2011;Nascimbeni & Burgos, 2016; …”
Section: Open Educational Practices (Oep)mentioning
confidence: 99%
“…Research studies deal with this broad definition of OEP in various ways. Some focus primarily on the OER aspects of OEP (Armellini & Nie, 2013;Atenas, Havemann, & Priego, 2014;Hogan, Carlson, & Kirk, 2015;Karunanayaka, Naidu, Rajendra, & Ratnayake, 2015;Murphy, 2013;Schreurs et al, 2014). Other studies explore broader aspects of OEP such as open pedagogies and learning in open networks (Casey & Evans, 2011;Nascimbeni & Burgos, 2016; …”
Section: Open Educational Practices (Oep)mentioning
confidence: 99%
“…In academic contexts, open practices take three main forms, " (1) (Veletsianos & Kimmons, 2012a, p. 2), and include teaching, learning, and research activities. In instruction, they frequently (though not exclusively) include the creation, use, re-use, adaptation, and dissemination of open educational resources (Armellini & Nie, 2013;Murphy, 2013;Nikoi & Armellini, 2012;Tuomi, 2013;UNESCO, 2002).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The Babson report -a survey of over 2,100 US teaching faculty conducted by Allen and Seaman (2014) -also reported that the most significant barrier to more widespread adoption of OER by faculty was the perception that too much time and effort was required to locate and evaluate the material. Okonkwo (2012) and Armellini and Nie (2013) found that, though teaching faculty are willing to use OER, lack of technical skills limits their abilities to adapt and use OER. Though Mtebe and…”
Section: Obstacles To the Adoption Of Oermentioning
confidence: 99%